Ceriantharia in current systematics: Life cycles, morphology and genetics - Stampar, Sérgio N. [UNESP]; Maronna, Maximiliano M.; Kitahara, Marcelo V.; Reimer, James D.; Beneti, Julia S.; Morandini, André C. (Springer Nature, 2016)
The systematics of the class Anthozoa has been built-up by a number of authors with different approaches. However, despite all efforts the evolutionary position of the tube-dwelling anemones (subclass/order Ceriantharia) remains unclear. This dilemma has arisen especially due to lack of understanding of the homologies that date back to the early twentieth century. Thus, this review focuses on discussing the morphological and genetic patterns and inferences of Ceriantharia in relation to other groups of Anthozoa. Initially we discuss the basic aspects of Ceriantharia, followed by a comparison of ceriantharian characters to other anthozoan groups and also provide a discussion on the uncertain systematic and evolutionary position of the order bringing up some perspectives on future studies of Ceriantharia.
Keywords: Anthozoa; Cnidaria; Integrative taxonomy; Morphology; Phylogenetics; Tube dwelling anemones